JURISPRUDENTIAL DEVELOPMENTS ON THE REASONING OF THE ADMINISTRATIVE ACT - Elena Emilia ȘTEFAN (Challenges of the Knowledge Society)
The activity of public authorities is subject to the control of legality performed by the administrative courts, according to the law. On the basis of art. 52 of the Constitution, persons aggrieved in their legitimate rights and interests often complain before the courts that the administration fails to give reasoning on the administrative acts. At EU level, the Charter of Fundamental Rights of the European Union stipulates that giving reasons for administrative acts is a component of the right to good administration. In this context, the aim of this paper is to analyze the relevant case-law in order to be able to observe the national administrative contentious judge's opinion on the reasoning of administrative acts, in the sense of whether this formality is mandatory or not for the issuing public authority. In terms of the research methodology, the structure of the paper has two main components, a theoretical one, namely it will describe the state of the legislation applicable to the reasoning of administrative acts, then it will focus on the practical component, in order to understand what problems arise in the work of public administration in this aspect. The proposed subject is topical, practical and of general interest. Using specific legal methods, the conclusion of the paper will be emphasized, namely that the reasoning is a condition for the legality of the administrative act, without which the proper functioning of public administration would be questioned.